Variability of subtidal flow in a narrow meandering stratified estuary. (5th March 2022) - Defontaine, Sophie; Walther, Régis; Sous, Damien
Abstract: A 3D numerical model was set up to investigate the spatial and temporal variations of subtidal circulation in a narrow meandering stratified estuary: the Adour Estuary (France). The hydrodynamic model was validated with field data and reproduced satisfactorily tide, current and salinity observations. The results highlighted a fortnightly switch in the residual flow structure and a variation in residual circulation intensity between low and high river discharge conditions. During neap tides, an exchange flow was observed as the baroclinicity dominated the residual circulation. During spring tides, the advection and barotropic pressure gradient drove the subtidal flow and an outflow over the whole water column took place. Residual flows were twice as high during high river discharge as during low river discharge. Secondary cross-channel residual circulation was driven by the estuarine morphology and the along-channel residual circulation. A secondary circulation cell was observed when a density-driven exchange flow occurred (neap tide). The meanders induced a variation of the sense of rotation of the circulation cell. A constriction of the channel has been shown to strengthen the residual circulation by flow conservation. Finally, we observed that the freshwater Froude number and the Mixing number Geyer and MacCready (2014) were able to distinguish residual flow pattern between idealised simulation cases. Highlights: A fortnightly switch in the residual flow structure is revealed in the Adour Estuary. Residual flows were twice as high during high river flow as during low river flow. Topographic effects are not dominant in a narrow stratified estuary. Dimensionless numbers are able to distinguish residual flow pattern.